Talking around embodiment: the views of GPs following participation in medical anthropology courses. Issue 1 (10th June 2004) - Jaye, C
Abstract : Objectives: To explore the ways in which general practitioners talk around the concept of "embodiment" after participating in introductory courses in medical anthropology, and to contribute to the debate about what persons and bodies mean for biomedicine. Design: This study used a qualitative interview methodology. Participants: Participants were general practitioners who had all completed at least one introductory course in medical anthropology. Results: In talking around embodiment, respondents articulated several interconnected dimensions of meaning. These included a Cartesian derived perspective of personhood involving complex relationships between intertwined components of soul, body, and mind; phenomenological perspectives on experience; the social meanings of the body; the ways in which individual bodies are acted upon by regulatory social and political bodies, and an implicit articulation of embodiment as relational, fluid, and processual. A theme of integrity or wholeness was discernible as a common thread linking all these understandings. Conclusions: Critical interpretive medical anthropology crosses social science and humanities boundaries with its explicit orientation around the paradigm of embodiment as a means of understanding lived experience, social and personal meanings of the body, and the political economy of the body. Perhaps its major contribution to postgraduate medical education is its power to encourage or facilitate reflection that is grounded in practice. This study shows that it is possible for medical practitioners to problematise the Cartesianism of biomedicine and its effects on both patients and doctors, and to conceptualise the integrative framework encapsulated in the notion of embodiment as lived medicine.